EFFECT OF REVERSE BIOFLOC SYSTEM WATER QUALITY ON GROWTH AND SURVIVAL OF RED TILAPIA (Oreochromis niloticus) IN CIANJUR, WEST JAVA - Putri, Rahma Windy Sah; Iskandar, Iskandar; Rostika, Rita; Siswoyo, Siswoyo; Priorwirjanto, Gatot Hari (Asian Journal of Aquatic Sciences, 2025)
This study aims to determine the effect of a reverse biofloc system on the water quality, growth, and survival of red tilapia (Oreochromis niloticus). The research method is experimental with a completely randomized design (CRD). The containers used were 13 buckets with a capacity of 100 L, with one control and three treatments, each repeated four times. Each container was filled with 10 red tilapia fish. Treatments included probiotics with doses of 5 mL, 10 mL, and 15 mL. The results showed that the treatment with 15 mL probiotics produced the highest fish weight growth, with an average of 558.75 g and an average length growth of 9.1 cm. Analysis of variance (ANOVA) showed significant differences in fish weight and length growth, indicating that probiotic concentration influenced fish growth. All treatments' survival rates (SR) reached 100%, indicating that the inverted biofloc system can maintain optimal environmental conditions. Water quality in the reverse biofloc system did not significantly affect fish growth, so other factors, such as microorganism density and nutrient availability, played a role. This study concludes that the reverse biofloc system with the addition of 15 mL probiotics provides the best results in increasing the growth of red tilapia without affecting its survival.